(untitled) (UNED Research Journal, 2017)
Glochidia larvae from Anodonta luteola were observed in gills of Oreochromis niloticus from a farm in Cañas, Guanacaste. Samples were taken and analyzed by electron microscopy (SEM) and light microscopy. Glochidia were 311, 8μm total length (TL), 331,7μm total height (TH), and 251,1μm hinge dorsal length (HDL). Anodonta has 21 species reported for the Panamica province, and A. luteola has five synonyms, often used in different reports.